Anthropometric characteristics and competition dietary intakes of professional rugby league players - Lundy, B.; O'Connor, H.; Pelly, F.; Caterson, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study aimed to describe the physique characteristics and competition nutrient intake of professional Rugby League players and to assess use of a statistical technique for evaluating validity of dietary reporting. Players (n = 74) were endomorphic mesomorphs and had a mean weight, height, and BMI of 93.4 ± 10.9 kg, 179.9 ± 7.3 cm, and 28.5 ± 2.1 kg/m2 respectively. Mean sum of eight skinfolds was 78.9 ± 2.2 mm (12.4 ± 2.9% fat). Players (n = 34) reported a mean daily energy intake of 17,708 ± 3,688 kJ (carbohydrate 51%, protein 18%, fat 25%, alcohol 4%) with 6 and 2.0 g · kg-1 · d-1 from carbohydrate and protein respectively. Micronutrient intake was adequate but alcohol consumption was high relative to health standards. The dietary records provided a plausible estimate of energy intake however further research is required to evaluate statistical techniques for assessing dietary validity in athlete groups.